1996
DOI: 10.3109/03008209609000700
|View full text |Cite
|
Sign up to set email alerts
|

Collagen and Proteoglycan Production by Bovine Fetal and Adult Chondrocytes Under Low Levels of Calcium and Zinc Ions

Abstract: The experiments described herein tested the effects of CaCl2 and ZnCl2, added at various concentrations in the culture medium, upon the synthesis of collagen and proteoglycan by adult and fetal (articular, epiphyseal and hypertrophic) bovine chondrocytes maintained in high density multilayer cultures. CaCl2 concentrations below 0.5 mM or the addition of 1-50 microM ZnCl2 to the medium selectively promoted the production of collagen by all four populations of chondrocytes but had no effect on fibroblasts. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Collagen production was reported to be the lowest at [Ca 2+ ] = 1 to 2mM in a chondrocyte-monolayer study, and an increase of [Ca 2+ ] from 2mM stimulated collagen production [12]. Other studies show that a lower calcium level can stimulate the Type X collagen synthesis and suppress the Type I collagen synthesis while leaving the Type II collagen unchanged [46,47].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Collagen production was reported to be the lowest at [Ca 2+ ] = 1 to 2mM in a chondrocyte-monolayer study, and an increase of [Ca 2+ ] from 2mM stimulated collagen production [12]. Other studies show that a lower calcium level can stimulate the Type X collagen synthesis and suppress the Type I collagen synthesis while leaving the Type II collagen unchanged [46,47].…”
Section: Discussionmentioning
confidence: 98%
“…These ions bind to proteoglycans by electrostatic force to maintain structure and function of the tissue [11]. Thus calcium metabolism and the changes in calcium ion concentration are important during the cartilage development and under pathological conditions [12]. In particular, the calcium level in synovial fluid of human knee joints has been reported to be 4mM or higher [13], while (inexplicably) most previous studies have been performed in culture medium with a [Ca 2+ ] of 1.8mM.…”
Section: Introductionmentioning
confidence: 94%
“…CaCl 2 levels have been shown to be important in maintaining the cartilage phenotype. 48,49 CaCl 2 was therefore removed from the cultures for the last 14 days and gels maintained stability, which might be attributed to the high cell proliferation and matrix synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it was reported that lowering molecular weight. In contrast, pretreatment of anti-cFos antibody did not reduce the signals of DNA-binding the calcium concentration of the culture medium did not alter the DNA synthesis [18], and that after confluence proteins bound to AP-1 sequences ( fig. 14).…”
Section: Bmentioning
confidence: 98%